Risk Based Banking Financial Performance Impact on PSAK 71 Implementation (Study at Bank Mega Tbk.) - Parashtiwi, Ninggar (Terbuka Journal of Economics and Business, 2021)
This study to examine the effect of PSAK 71 to banking performance based on Bank Mega Tbk. Banking performance component is risk profile, good corporate governance, earnings, and capital. The research data used secondary collected through the documentation method. The data collection used library research. The results of this study showed that risk profile with NPL ratio and LDR ratio had an impact decrease in the percentage ratio after PSAK 71. Good corporate governance have not an impact after PSAK 71. Earnings with ROA ratio and ROE ratio have not an impact after PSAK 71, but BOPO ratio and NIM ratio had an impact decrease in the percentage ratio after PSAK 71. Capital has not an impact after PSAK 71.